Awareness, attitude, and practice towards cancer cervix prevention among rural women in southern India: A community-based study - Supriti Ghosh; Sneha D. Mallya; Sanjay M. Pattanshetty; Deeksha Pandey; Veena G. Kamath; Shama Prasada Kabekkodu; Kapaettu Satyamoorthy; Ranjitha S. Shetty (Elsevier, 2024)
Problem considered: Cervical cancer is a major public health problem among women worldwide and it is the second most common cancer among women in India. The present study was conducted to assess awareness, attitudes, and practices towards cervical cancer and its prevention among rural women in southern India. Methods: This community-based study was carried out from January to December 2017 among 1100 married women aged 20-65 years residing in southern Karnataka, India. A household survey was undertaken, and eligible women were interviewed using a pre-designed questionnaire. The socio-demographic details of the women and their awareness, attitude, and practices towards cervical cancer prevention and screening were documented. The association of women's knowledge adequacy with their socio-demographic factors was evaluated and is expressed as odds ratios with 95% confidence intervals. Results: About 67% of the participants had heard the term "cervical cancer" earlier and 47.9% of them were aware that cervical cancer is preventable. Poor genital hygiene (41.4%) and early age at sexual intercourse (35.4%) were the commonly quoted risk factors for cervical cancer. Only 35.7% of participants had adequate awareness regarding cervical cancer screening and it was significantly associated with their age, education level, employment, and socio-economic status. The majority (99%) of women had a favorable attitude toward cervical cancer screening though it failed to translate into practices. Conclusions: Despite a favorable attitude, awareness and practice towards cervical cancer prevention were suboptimal. Periodic awareness programs and ensuring access to cervical cancer screening are crucial in this context.